Description of Metacognitive Awareness of Chemistry Education Students on Basic Chemistry Teaching Skill - Sari, Widyan; Hairida, Hairida; Ulfah, Maria; Junanto, Tulus; Rasmawan, Rahmat (IKIP PGRI Bojonegoro, 2024)
This study seeks to describe the metacognitive awareness of prospective chemistry teacher students in learning. This study aims to describe the metacognitive awareness of chemistry education students in the basic ability to teach chemistry subject. This type of research is descriptive research with a quantitative approach. This research questionnaire is a modified MAI instrument. The result of the validity test and reliability test of the instrument found that 50 of the 52 MAI instrument statements were valid (the reproducibility coefficient value was 0,90 and the scalability coefficient value was 0,79) and quite reliable (with a value of (0,458). The results of the research data analysis showed that the overall proportion of students’ metacognitive awareness was 82,825% in the good category. This indicates that students are aware of their own thinking and can distinguish the stages of elaboration input and output of their own thoughts.